Studi Pemodelan Distribusi Konduktivitas Bawah Permukaan 3-D Berbasis Data Resistivitas Menggunakan Program Aplikasi DCIP3D Versi 2.1 - Nadhia Fairuz Syafira; Sitti Ahmiatri Saptari; Adhika Junara Karunianto (Al-Fiziya: Journal of Materials Science, Geophysics, Instrumentation and Theoretical Physics, 2019)
Human needs will increase in various aspects, including the need for content in the earth. In describing the distribution of physical properties beneath the earth's surface, 3-D modeling is the best way to find out the details of the subsurface content of the earth. To facilitate the making of 3-D models from the earth, the DCIP3D application program is used. DCIP3D develops a series of inversion algorithms to restore 3-D conductivity models. The research was conducted to optimize the use of DCIP3D version 2.1. The data used are secondary and synthetic data. Secondary data is resistivity geoelectric data consisting of four line of the results of the PTBGN-BATAN survey in the Ahu Mamuju, West Sulawesi, 2017. Data processing is done by making mesh cell size which is a discritization of the earth model. The variation of the mesh core size is done (5 × 5 × 5) m, (10 × 10 × 10) m and (15 × 15 × 15) m. By completing various input files for DCIP3D, the 3-D subsurface conductivity model was successfully restored. Adding topographic values to the model causes the model to look even more real. The best model that describes the conductivity of the secondary data survey area is a model with a core cell (10 × 10 × 10) m because it corresponds to the distance between the electrodes used during data acquisition.